A Heart‐Breast Cancer‐on‐a‐Chip Platform for Disease Modeling and Monitoring of Cardiotoxicity Induced by Cancer Chemotherapy. Issue 15 (23rd October 2020) - Lee, Junmin; Mehrotra, Shreya; Zare‐Eelanjegh, Elaheh; Rodrigues, Raquel O.; Akbarinejad, Alireza; Ge, David; Amato, Luca; Kiaee, Kiavash; Fang, YongCong; Rosenkranz, Aliza; Keung, Wendy; Mandal, Biman B.; et al.
Abstract: Cardiotoxicity is one of the most serious side effects of cancer chemotherapy. Current approaches to monitoring of chemotherapy‐induced cardiotoxicity (CIC) as well as model systems that develop in vivo or in vitro CIC platforms fail to notice early signs of CIC. Moreover, breast cancer (BC) patients with preexisting cardiac dysfunctions may lead to different incident levels of CIC. Here, a model is presented for investigating CIC where not only induced pluripotent stem cell (iPSC)‐derived cardiac tissues are interacted with BC tissues on a dual‐organ platform, but electrochemical immuno‐aptasensors can also monitor cell‐secreted multiple biomarkers. Fibrotic stages of iPSC‐derived cardiac tissues are promoted with a supplement of transforming growth factor‐β 1 to assess the differential functionality in healthy and fibrotic cardiac tissues after treatment with doxorubicin (DOX). The production trend of biomarkers evaluated by using the immuno‐aptasensors well‐matches the outcomes from conventional enzyme‐linked immunosorbent assay, demonstrating the accuracy of the authors' sensing platform with much higher sensitivity and lower detection limits for early monitoring of CIC and BC progression. Furthermore, the versatility of this platform is demonstrated by applying a nanoparticle‐based DOX‐delivery system. The proposed platform would potentially help allow early detection and prediction of CIC in individual patients in the future. Abstract : In this paper, a cardiotoxicity‐on‐a‐chip platform containing induced pluripotent stem cell‐derived cardiac tissue communicating with breast cancer tissue is presented with electrochemical immuno‐aptasensors for non‐invasively monitoring cell secreted biomarkers. The suggested platform is capable of differentiating functionality and toxicity in healthy/fibrotic cardiac tissues after treatment with chemotherapy to step toward early detection and prediction of cardiotoxicity in individual patients.